STRONG MOTION TIME-HISTORY FOR STORAGE TANKS BY USING SEVEN DIFFERENT EARTHQUAKE ACCELEROGRAMS - Zacchei, Enrico; Brasil, Reyolando M. L. R. F. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper aims to describe the seismic performance of circular oil storage tanks by calculating the total base shear induced from each seismic horizontal acceleration: magnitude varies between 6 and 8, and depth from 0 km to 35 km. Time-history analysis has been made considering that the stresses are not excited at the same time. The equations used are in accordance to Eurocode 8 and for the response spectra seven different accelerograms of seven different stations have been considered. The main objective is to provide an approach that describes many important seismic actions in tanks as well as their implications for the dynamic analysis of structural instability. Despite the area of oil being considerably discussed, there are few studies on this topic in Brazil. The results of the analysis show the importance to study the dynamic action and its effects. Keywords: Response time-history, Seismic action, Oil storage tanks, Structural engineering